Dispute on Inherited Land for Sale: (Analysis of Supreme Court Decision No. 102/Pdt.G/2018/Pn.Mdn) - Celine, Celine; Salim, Filbert; Jennifer, Tenny; Ramadhana, Widodo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The transfer of rights to land is a legal act that results in the transfer of rights from one legal subject to another which can be carried out through the procedures of buying and selling, inheritance and grants. The right to land can be imposed dependent rights that have a material nature (zaaksgevolg) where the right always follows the object. This research uses descriptive qualitative research methods and types of normative legal research that examines the Civil Code, applicable laws and regulations including Basic Agrarian Regulations (Law No. 5 of 1960), Dependent Rights (Law No. 4 of 1996), Land Registration (PP No. 24 of 1997). The transfer of rights to land which is the object of dependent rights in the disputed inheritance provides an explanation of the procedure for transferring rights to land by sale and purchase and inheritance and the protection of parties makes clear the ownership of rights to disputed land. Keywords: Transfer of Land Rights, Dependent Rights, Buying and Selling, Inheritance